Buddhist Universities and Learning Management in the 21st Century - et. al., Poolsak Homsombat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The learning management in the 21st century for Buddhist universities in Thailand is highly important to develop competencies of learners for being able to learn, live their life in the society, live together with other people including applying these knowledge and understanding to the changing society in an appropriate, balance and sustainable manners, consistent with the intention of Buddhism educational management, integration with new sciences, mind and society development being task burden of Buddhist universities. This academic article therefore aimed to propose an idea and guidelines of learning management in the 21st century for Buddhist universities in Thailand. This study was carried out by means of the qualitative research methodology (documentary research) and the obtained data were verified by Focus Group Discussion (FGD) of six scholars from the faculties of Education, Buddhism, Social Sciences. The obtain data were interpreted by means of the descriptive analysis together with the inductive reasoning method. The study results revealed that significant guidelines of learning management in the 21st century for Buddhist universities are: (1) promoting the quality of teaching and learning of instructors in higher education institutions, (2) enhancing 3R 8C skill in learners, (3) enhancing C-Teacher skill in instructors, (4) integrating Buddhist methods of teaching with learning management.